Prazosin for the management of behavioural and psychological symptoms of dementia - Rajesh R Tampi; Deena J Tampi; Syeda Arshiya Farheen; Mahwish Adnan; Dhweeja Dasarathy (BioExcel Publishing Ltd, 2022)
Prazosin, a centrally acting α1 adrenoceptor antagonist, has been included in two published algorithms amongst the list of medications that may be used in the management of behavioural and psychological symptoms of dementia (BPSD). However, a review of PubMed, Ovid and Cochrane Collaboration found that there was only one small published randomized controlled trial (RCT) that evaluated the use of prazosin amongst individuals with BPSD. Evidence from this good quality RCT indicates that prazosin appears to benefit individuals with agitation and aggression amongst individuals with BPSD and this medication is well tolerated. When compared to other treatments for BPSD, including atypical antipsychotics, antidepressants, acetylcholinesterase inhibitors, memantine, repetitive transcranial magnetic stimulation and electroconvulsive therapy, where there are multiple studies for each of these treatment modalities, the data for the use of prazosin for BPSD are limited to just one good quality RCT. Given the limitations in available data, the routine use of prazosin for the treatment of BPSD cannot be recommended at this time. However, prazosin may be used for the management of agitation and aggression amongst individuals with dementia when other medication classes, like acetylcholinesterase inhibitors, memantine, antidepressants and/or atypical antipsychotics, have been ineffective or not tolerated.